Do Macroeconomic Factors Significantly Affect Economic Growth? Evidence from Ghana - Evans Yeboah; Dastan Bamwesigye (Acta Economica)
Macroeconomics examines the whole economy using some indicators like investment, exchange rate, unemployment rate, and trade. These indicators contribute to economic growth either positively or negatively. After Ghana's economic reforms in 1984, its economy underwent a series of transformations which have impacted the economy in one way or the other. The study investigated some selected macroeconomic variables (external debt, FDI, inflation, exchange rate, and trade openness) that impact Ghana's economic growth. The study analyzed time series data from the World Bank (1991 to 2021) using econometrics methods; the Johansen cointegration, Ordinary least squares (OLS), and the distributed lagged model. The cointegration result showed that there is a long-run relationship between the variables. The outcome of the OLS indicated that external debt, FDI, and trade openness had a positive impact, whereas inflation and unemployment rates had a negative effect using GDP as a proxy for economic growth. The outcome also showed that real exchange has no significant effect on the economy of Ghana. On the contrary, the findings from a distributed lagged model provided evidence that inflation, external debt, and FDI impact spreads over some period. We recommend that the government of Ghana invests the external loans into sectors capable of increasing the growth of the economy and providing investment incentives to attract more investors.